2007
DOI: 10.1002/jso.20820
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tumor blood flow assessed by perfusion CT and effect of neoadjuvant therapy in advanced esophageal cancers

Abstract: Tumor BF by perfusion CT can partly predict the effect of ChT and CRT and survival. Further large cohort studies in homogeneous patient groups will reveal its clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Park et al [15] performed a prospective study to determine whether perfusion parameters could predict the response of pancreatic cancer to concurrent chemotherapy and radiation therapy and showed that responders had higher BV, but this difference was not significant. Makari et al [22] investigated the relationship between perfusion parameters and the effect of neoadjuvant therapy in advanced oesophageal cancers and demonstrated that high BF and low MTT correlated significantly with a good response. Petralia et al [12] assessed the potential of perfusion parameters for monitoring induction chemotherapy in patients with squamous cell carcinoma of the upper aerodigestive tract, and showed that the baseline tumour BV was significantly higher in responders than in nonresponders, and that there were no significant differences in the other perfusion parameters between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Park et al [15] performed a prospective study to determine whether perfusion parameters could predict the response of pancreatic cancer to concurrent chemotherapy and radiation therapy and showed that responders had higher BV, but this difference was not significant. Makari et al [22] investigated the relationship between perfusion parameters and the effect of neoadjuvant therapy in advanced oesophageal cancers and demonstrated that high BF and low MTT correlated significantly with a good response. Petralia et al [12] assessed the potential of perfusion parameters for monitoring induction chemotherapy in patients with squamous cell carcinoma of the upper aerodigestive tract, and showed that the baseline tumour BV was significantly higher in responders than in nonresponders, and that there were no significant differences in the other perfusion parameters between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…The technique has been applied in several types of tumors, including those of the prostate (6), colon and rectum (7)(8)(9)(10)(11)(12), head and neck (13)(14)(15), lung (16)(17)(18), and liver (19)(20)(21)(22), and also in normal tissue for control purposes and in diffuse parenchymal diseases (eg, cirrhosis). A variety of imaging protocols have been used, and in particular, the acquisition durations in these studies have varied from 30 to 480 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Our data acquisition period was nearly 10 minutes, but it appeared to be insufficient to attain stabilization in PS with high confidence. Further studies extending (7,(9)(10)(11)(13)(14)(15)(16)(17)19,21,22,28). Although these studies did not all include the specific organ and tissues we used, some of these studies may not have characterized the CT perfusion parameters adequately.…”
Section: Gastrointestinal Imaging: Metastases To the Liver From Neuromentioning
confidence: 99%
“…It has been reported that CT perfusion is useful for diagnostic, prognostic, and monitoring purposes in oncology, prior and after the anticancer therapy [1][2][3][4][5][6][7][8][9][10][11][12][13]. Thus, the values of certain quantitative perfusion parameters, which could be used in the oncology practice to discriminate the neoplasm from the normal tissues, malignant from benign lesions, and potential or actual responders to the anticancer therapy from non-responders, are provided in the available literature [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%